Isolation and in vitro Characterization of Actinobacteria from Coastal Soils Against Pathogenic Vibrios for Use as Probiotics in Aquaculture - García-Bernal, Milagro; Medina-Marrero, Ricardo; Murillo-Amador, Bernardo; Campa-Córdova, Ángel Isidro; Tovar-Ramírez, Dariel; Mazón-Suástegui, José Manuel (REVISTA TERRA LATINOAMERICANA, 2025)
The use of probiotic bacteria has global importance in aquaculture and aquaponics because they improve growth rates and enhance the organisms resistance to disease, thus increasing production. This study aimed to isolate and characterize actinomycete strains from marine–coastal soils on both coasts of Mexico and to evaluate them in vitro against marine pathogens to determine their probiotic potential and applicability in aquaculture and aquaponics. Fif ty-four actinomycete strains were isolated, and 14 of them exhibited antibacterial activity against the evaluated Vibrio spp. species [V. alginolyticus (CIAD-CAIM 57), V. parahaemolyticus (ATCC-17802), V. harveyi (CIAD-CAIM 1793), and V. vulnificus (CIAD-CAIM 157)]. Based on the results, strain M4 was selected and characterized according to its morphological and biochemical traits. This strain showed enzymatic activity in vitro, confirming its probiotic potential and applicability in aquaculture; it also exhibited increased activity against the pathogenic vibrios tested. These results suggest that strain M4, isolated from coastal marine soil, has probiotic potential and could serve as an alternative to antibiotics to mitigate pathogen attacks in agroaquaculture production systems.